Answer:
x=-1
y=-1
Step-by-step explanation:
-6x + 5y =1 ......equation (1)
6x + 4y = –10 ......equation (2)
adding equation (1) to equation (2)
9y=-9
9y/9 =-9/9 (dividing both side by the coefficient of y)
y=-1
subtituting the value of y =-1 into equation (2)
6x+4(-1)=-10
6x+(-4)=-10
6x-4=-10
6x=-10+4(making constant to be at one side and the variable at the other side)
6x=-6
x=-6/6
x=-1
Hey
The Answer is -4x
Heres the Step by Step work
You add 14 to each side because it is negative, so
5x-14=-34
+14|+14
and you will end up with
5x=-20
Divide 5 on each side, so
5x=-20
/5x | /5x
-20 / 5x =
x=-4
or
-4x
mark branliest plz
Hello.
C) x=4π/3
The variable x in the cotangent argument has a unit coefficient, so the period is π, just as it is in the parent function cot(x).
Can you graph y = cot(x)? By subtracting the constant π/6 from the argument, that graph is translated to the right by π/6. Just as with cot(x), it is decreasing everywhere.
Have a nice day